Factors Related to Contact Dermatitis Symptoms in Sorting Workers at The Talang Gulo TPA - Isti Fardilah; Puspita Sari; Oka Lesmana S. (Lembaga Pengembangan Kinerja Dosen, 2024)
Based on Indonesian epidemiological data, 66.3% of 97% of cases are irritant contact dermatitis. Data from the Jambi Provincial Health Service in 2020, the percentage of contact dermatitis was 4.98% and in 2022 it will increase by 5.96%. The aim of this research is to determine the factors associated with symptoms of contact dermatitis in sorting officers at Talang Gulo TPA, Jambi City in 2024. This research is a quantitative study using a cross sectional study design. The technique used in this research sample was total sampling, the sample size was 40 respondents. From the results of this study, the symptoms of contact dermatitis in sorting officers were 12% symptomatic and 70% asymptomatic. Factors related to symptoms of contact dermatitis in sorting officers at Talang Gulo TPA were skin cleanliness (p value = 0.000), personal hygiene (p value = 0.001), and cleanliness of clothing (p value = 0.003) and those that were not related to dermatitis symptoms contact, habit of using APD (p value = 0.142). It was found that skin cleanliness, personal hygiene, and cleanliness of clothing were related to symptoms of dermatitis at Talang Gulo TPA, Jambi City.